Blood flow restriction combined with resistance training on muscle strength and thickness improvement in young adults: a systematic review, meta-analysis, and meta-regression - Ma, Feier; He, Jianghua; Wang, Yan (Frontiers in Physiology, 2024)
Background: High-intensity resistance training is known to be the most effective method for enhancing muscle strength and thickness, but it carries potential injury risks. Blood flow restriction (BFR) combined with resistance training has been proposed as a safer alternative method for improving muscle strength and thickness. Methods: A meta-analysis was conducted, including 20 studies from five databases that met the inclusion criteria, to assess the efficacy of BFR combined with resistance training compared to traditional resistance training (NOBFR). The analysis focused on changes in muscle strength and thickness. Subgroup analysis and meta-regression were performed to explore the effects of tourniquet width and pressure. Results: The findings showed that BFR combined with resistance training is comparable to traditional resistance training in enhancing muscle strength (0.11, 95%CI: [-0.08 to 0.29], I² = 0%) and muscle thickness (-0.07, 95% CI: [-0.25 to 0.12], I² = 0%). Subgroup analysis indicated no significant differences in muscle strength (P = 0.66) and thickness (P = 0.87) between low-intensity BFR training and other intensity levels. Meta-regression suggested that tourniquet width and pressure might affect intervention outcomes, although the effects were not statistically significant (P > 0.05). Conclusion: BFR combined with resistance training offers a viable alternative to high-intensity resistance training with reduced injury risks. We recommend interventions of 2-3 sessions per week at 20-40% of 1 RM, using a wider cuff and applying an arterial occlusion pressure of 50-80% to potentially enhance muscle strength and thickness. It is also recommended to release tourniquet pressure during rest intervals to alleviate discomfort. This protocol effectively improves muscle strength with minimal cardiac workload and reduced risk of adverse events.